Pengaruh Podcast Habib Ja’far Dalam Dakwah Islam Di Era Digital Untuk Membentuk Karakter Gen Z Yang Bertaqwa. - Maulani, Aulia Syakinah; Kharismatika, Danella; Anggraeni, Hany Dwi; Ristiyaningsih, Sukma Ayu; Fajrussalam, Hisny; Putri, Hafizyani Eka (Mu'ashir: Jurnal Dakwah dan Komunikasi Islam, 2025)
This study analyzes the influence of Habib Ja’far’s podcast as an Islamic da’wah medium in the digital era to shape a pious Gen Z character. The research employed a descriptive quantitative method, collecting data through Likert-scale questionnaires from 33 Gen Z respondents in Purwakarta Regency. The results indicate a strong positive correlation between the podcast’s role and the formation of Gen Z’s character, with a correlation value of 0.642. The coefficient of determination (41.2%) highlights the podcast's significant contribution to developing Islamic values among Gen Z. Habib Ja’far’s humorous, inclusive, and relatable preaching style is a key factor in the podcast’s success. This research underscores the importance of innovative da’wah strategies in the digital age to reach younger generations. Habib Ja’far’s podcast is recommended as an effective educational medium for delivering inspiring Islamic messages and fostering a pious character.